Upaya Penegakan Hukum terhadap Pelanggaran Berat Hak Asasi Manusia (Studi terhadap Agresi Militer Amerika Serikat Tahun 2003 di Irak) - Tahir, Achmad (Asy-Syir'ah: Jurnal Ilmu Syari'ah dan Hukum, 2008)
Gross  violation  of  human  rights  has  always  been stalking the world. Wars in Iraq and Palestine not only devastate buildings and infrastructure, but also above all that take the toll of thousands of civilians whose lives are supposed to be protected. United States, all this time claiming as the greatest democracy and champion of human rights, apparently is the one that  inflict worst injury to democracy and human rights themselves, as  apparent in the fact that until today the issues of wars in Iraq  and Palestine are yet to be settled. The United Nations, in its ideal  vision the spearhead of justice in global level, is in actuality cowering before the  United  States  and  its allies.  Sad  but  true,  Law  becomes powerless in the face of ambitions of global political power.